2022
DOI: 10.1097/hcr.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, Facilitators, and Barriers of Alternative Models of Cardiac Rehabilitation

Abstract: We conducted a systematic review of qualitative studies examining patient perspectives of cardiac rehabilitation (CR) models that use either an alternative location (ie, home-based) and/or an alternative exercise. Benefits, facilitators, and barriers were reported by patients. These insights can help improve the delivery of CR and provide new directions for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…In both participants and non-participants of cardiac rehabilitation, the main facilitator for remote cardiac rehabilitation was the alleviation of transport, and the main barrier was digital literacy. This view is shared by a recent qualitative systematic review on alternative cardiac rehabilitation, which confirmed peer and family support and convenience as facilitators and weather and digital literacy as barriers [ 44 ]. To overcome this digital divide, it is therefore important to upskill those wishing to attend remotely in digital literacy, co-design culturally competent services and promote wider access to digital technology [ 37 , 38 ].…”
Section: Pandemic Experience and Participant Preferencementioning
confidence: 87%
See 1 more Smart Citation
“…In both participants and non-participants of cardiac rehabilitation, the main facilitator for remote cardiac rehabilitation was the alleviation of transport, and the main barrier was digital literacy. This view is shared by a recent qualitative systematic review on alternative cardiac rehabilitation, which confirmed peer and family support and convenience as facilitators and weather and digital literacy as barriers [ 44 ]. To overcome this digital divide, it is therefore important to upskill those wishing to attend remotely in digital literacy, co-design culturally competent services and promote wider access to digital technology [ 37 , 38 ].…”
Section: Pandemic Experience and Participant Preferencementioning
confidence: 87%
“…To overcome this digital divide, it is therefore important to upskill those wishing to attend remotely in digital literacy, co-design culturally competent services and promote wider access to digital technology [ 37 , 38 ]. Other suggested strategies to overcome participation barriers include engaging other participants to share stories, seeking technological assistance from family and friends [ 9 ] and creating an inclement weather plan [ 44 ].…”
Section: Pandemic Experience and Participant Preferencementioning
confidence: 99%
“…Platz et al 6 Regarding benefits, self-efficacy and lifestyle change were reported in all 25 studies. The second most prominent category was physical or health benefits followed by psychological improvements.…”
mentioning
confidence: 99%
“…Key aspects include family/peer support, sense of safety, and convenience. Taken together, the patient insights gleaned from the Platz el al 6 systematic review can provide opportunities to develop CR programming that is more accommodating, allowing increased accessibility to more individuals and improve the utilization of CR.…”
mentioning
confidence: 99%
See 1 more Smart Citation